Protective Immunity to Dengue Virus Induced by DNA Vaccines Encoding Nonstructural Proteins in a Lethal Challenge Immunocompetent Mouse Model - Alves, Rúbens Prince dos Santos; Andreata-Santos, Robert; de Freitas, Carla Longo; Pereira, Lennon Ramos; Fabris-Maeda, Denicar Lina Nascimento; Rodrigues-Jesus, Mônica Josiane; Pereira, Samuel Santos; Carvalho, Alexia Adrianne Venceslau Brito; Sales, Natiely Silva; Peron, Jean Pierre Schatzmann; Amorim, Jaime Henrique; Ferreira, Luís Carlos de Souza (Frontiers in Medical Technology, 2020)
Dengue virus represents the main arbovirus affecting humans, but there are no effective drugs or available worldwide licensed vaccine formulations capable of conferring full protection against the infection. Experimental studies and results generated after the release of the licensed anti-DENV vaccine demonstrated that induction of high-titer neutralizing antibodies does not represent the sole protection correlate and that, indeed, T cell-based immune responses plays a relevant role in the establishment of an immune protective state. In this context, this study aimed to further demonstrate protective features of immune responses elicited in immunocompetent C57BL/6 mice immunized with three plasmids encoding DENV2 nonstructural proteins (NS1, NS3, and NS5), which were subsequently challenged with a DENV2 strain naturally capable of inducing lethal encephalitis in immunocompetent mouse strains. The animals were immunized intramuscularly with the DNA vaccine mix and complete protection was observed among vaccinated mice. Vaccine induced protection correlated with the cytokine profiles expressed by spleen cells and brain-infiltrating mononuclear cells. The results confirm the pivotal role of cellular immune responses targeting nonstructural DENV proteins and validate the experimental model based on a DENV2 strain capable of infecting and killing immunocompetent mice as a tool for the evaluation of protective immunity induced by anti-DENV vaccines.